Fine‐needle aspirations of pancreatic serous cystadenomas: Improving diagnostic yield with cell blocks and α‐inhibin immunohistochemistry. Issue 1 (12th August 2013) - Salomao, Marcela; Remotti, Helen; Allendorf, John D.; Poneros, John M.; Sethi, Amrita; Gonda, Tamas A.; Saqi, Anjali
<x xml:space="preserve">Abstract</x> BACKGROUND The diagnosis of serous cystadenoma (SCA), a rare benign pancreatic neoplasm, can alter the management of patients with pancreatic masses. Although characteristic imaging findings and fluid chemical analysis have been described, SCAs are not always recognized preoperatively. Furthermore, scant cellular yield on fine‐needle aspiration (FNA) often leads to a nondiagnostic or nonspecific benign diagnosis. α‐Inhibin (AI), a sensitive marker for SCA, is infrequently required for diagnosis in surgical specimens due to their characteristic histologic appearance. The objective of the current study was to determine whether AI staining can improve SCA diagnosis on FNA specimens. METHODS Fifteen confirmed cases of SCA with prior FNA specimens were selected for this study. FNAs were evaluated for cellularity, cellular arrangement, and cytomorphology. Resection specimens were reviewed. RESULTS Of the 15 FNA cases, approximately 75% demonstrated scant cellularity (11 of 15 cases). On smears, the cells were arranged as flat sheets, corresponding to strips of cells on cell block sections. The cells were small and round to cuboidal, with clear cytoplasm; occasional plasmacytoid cells and oncocytic cells were identified. Flattened cells, corresponding to attenuated epithelial cells lining macrocysts on the resections, were also noted. Stromal fragments were present in 5 FNAs and correlated with the hyalinized stroma in the resection specimens. AI immunostaining was positive in 88% of cases (7 of 8 of cases), thereby supporting the diagnosis of SCA. CONCLUSIONS The results of the current study indicate that low cellularity and bland cytology are inherent to SCAs. Performing cell blocks and AI staining on FNA specimens is useful for establishing the diagnosis of SCA. An immunohistochemical panel including AI, chromogranin, and synaptophysin may enhance the diagnostic accuracy of pancreatic FNA specimens. Cancer (Cancer Cytopathol) 2014;122:33–39. © 2013 American Cancer Society.